1999
DOI: 10.1002/(sici)1099-0755(199909/10)9:5<441::aid-aqc359>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human activity on the aquatic macroflora of Llangorse Lake, South Wales

Abstract: 1. The first recorded effects of human activity on the aquatic flora of Llangorse Lake, South Wales, were the result of introductions of Elodea canadensis in the early 1900s and of Nymphoides peltata in 1936, altering the species balance of both submerged and floating plant communities. 2. The most significant impact on the lake in recent times has been effluent from the sewage treatment works, which discharged into the lake between the early 1950s and 1982, and the impact of a concurrent intensification of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…There is a general agreement in the literature about the rapid spread of M. spicatum, e.g. in North America or Great Britain (Boylen et al, 1999;Wade, 1999). The results of Agami and Waisel (2002) suggested that a competitive relationship exists between the submerged species Najas marina and M. spicatum, in accordance with our findings (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is a general agreement in the literature about the rapid spread of M. spicatum, e.g. in North America or Great Britain (Boylen et al, 1999;Wade, 1999). The results of Agami and Waisel (2002) suggested that a competitive relationship exists between the submerged species Najas marina and M. spicatum, in accordance with our findings (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported comparisons between the current species richness, abundance and distribution and historical levels of aquatic vegetation in lake ecosystem. These documented changes occurred mostly during the second half of the last century, in response to human impacts, mainly changes in water level (Egertson et al, 2004;Hellsten et al, 2006), eutrophication (Ozimek and Kowalczewski, 1984), the intensification of agriculture (Wade, 1999;Duigan et al, 2006), stocking of herbivorous fish (Hutorowicz and Dziedzic, 2008) and changes in land use along the lakeshores and catchments (Papastergiadou et al, 2007(Papastergiadou et al, , 2008Partanen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is critical to be able to disentangle the bijective interactions of natural and human determinants in influencing macrophyte distribution and dominance [12]. Several works have been done to investigate the contribution of human impacts on such changes [13][14][15][16][17]. On the contrary, only few studies have investigated non-nutrient drivers of macrophyte growth and distribution [18,19] or focused on their natural successional patterns [11,20].…”
Section: Introductionmentioning
confidence: 99%